2010
DOI: 10.1080/10345329.2010.12035882
|View full text |Cite
|
Sign up to set email alerts
|

Sacrosanct or Flawed: Risk, Accountability and Gender- Responsive Penal Politics

Abstract: This article argues that Canadian and many international discussions of gender responsive (GR) penality have substituted male normative criteria with a 'female norm' without much critical reflection on the implications of this development and its impact on women prisoners. GR penality is situated within a narrow politics of difference that posits an essentialist characterisation of women as relational, thereby resurrecting past debates about the politics of difference (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 51 publications
3
65
0
Order By: Relevance
“…23 Two factors seem to stand out: (1) women are deeply embedded in their prison lives and positive interactions with correctional staff and other inmates are critical to their sense of control over their lives and (2) productive time outside of their cells goes a long way toward increasing this sense of control and their overall sense of wellbeing. In terms of correctional programming, these findings suggest that prison administrators and staff need to become more attuned to the possibilities of and types of interactions women have in prison and, perhaps, less fixed on creating gender-specific standards for carceral life (Hannah-Moffat, 2010). The patterns of control women prisoners experience do vary across penal landscapes but the patterns of interaction that allow for some modicum of well-being remain largely consistent.…”
Section: Discussionmentioning
confidence: 85%
“…23 Two factors seem to stand out: (1) women are deeply embedded in their prison lives and positive interactions with correctional staff and other inmates are critical to their sense of control over their lives and (2) productive time outside of their cells goes a long way toward increasing this sense of control and their overall sense of wellbeing. In terms of correctional programming, these findings suggest that prison administrators and staff need to become more attuned to the possibilities of and types of interactions women have in prison and, perhaps, less fixed on creating gender-specific standards for carceral life (Hannah-Moffat, 2010). The patterns of control women prisoners experience do vary across penal landscapes but the patterns of interaction that allow for some modicum of well-being remain largely consistent.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, despite the women's various past victimization experiences, only a small number of them indicated that they began using meth to cope with victimization, and these individuals also insisted that the meth initiation was their choice. Finally, this failure to reflect the complexity inherent in women's pathways may support outdated treatment models that fail to adapt to changes in gender, substance use behaviors, and criminalization ( Author 1, 2013;Hannah-Moffat, 2010). There are therefore scholars who are calling to expand our understanding of women's substance abuse and crime and to acknowledge victimization as well as experiences of agency (Anderson, 2008;Ettorre, 2004).…”
Section: Women's Pathways To Crimementioning
confidence: 99%
“…Although mentoring services have been directed towards women, it is not clear what makes mentoring, as an intervention, unique or effective in responding to the structural difficulties that have contributed to many women's involvement in the criminal justice system. The majority of mentoring services referred to in existing literature focus on relationships and attitudes, and this approach has been criticised by some scholars for relying on an individualised framework that neither challenges nor accounts for the circumstances that precipitate women through the criminal justice system (Godkind , ; Hannah‐Moffat ; Pollack ). An individualistic framework is evident in services that emphasise the importance of outcomes in terms of building confidence, self‐esteem, and empowerment, with less consideration of circumstances and context; possibly a reflection of organisational remit rather than intent.…”
Section: Introductionmentioning
confidence: 99%